Identity securitization of local communities in the capital region nusantara - Sudiar, Sonny; Rauf, Abdul; Kurnia, Mahendra Putra; Helza, Zenobia Zalfanda (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
The study explores the security and securitization of indigenous peoples in Indonesia, highlighting the diverse ethnic groups and potential cultural erosion due to development. It aims to provide policy ideas for preserving their identity in the IKN Indonesia area. This qualitative field research in the IKN area of North Penajam Paser Regency, East Kalimantan Province, uses primary and secondary data to understand the situation of indigenous peoples. Data collection includes participant observation and in-depth interviews, while analysis uses a descriptive method. The Indonesian government should integrate societal security into its policies and strategies for the development of the IKN area, focusing on the collectivity of the Paser Balik community's identity. This is a form of state responsibility to ensure the community's existence, sustainability, and identity